2019
DOI: 10.1680/jadcr.17.00122
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion characterisation of Portland cement concrete and alkali-activated binders

Abstract: In this paper, alkali-activated binders (AAB) are investigated for their potential use as repair materials of Portland cement concrete (PCC). The adhesion characterization of PCC and repair materials using AAB made from fly ash (FA) and Portland cement (PC) activated with sodium hydroxide and sodium silicate solutions, AAB made from FA and calcium hydroxide (CH) activated with sodium hydroxide and sodium silicate solutions, and commercial repair material (RMs) have been investigated. Test results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
(30 reference statements)
0
16
0
1
Order By: Relevance
“…One of them is the alkali-activated binders that could produce from precursors consisting of Si 4+ and Al 3+ ions activated with a high alkali solution [7,8]. Many researchers [9][10][11][12] reported that the alkali-activated binders provided excellent mechanical and durability properties. Besides, alkali-activated binders showed a lower CO2 footprint than those of PC and epoxy-resin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is the alkali-activated binders that could produce from precursors consisting of Si 4+ and Al 3+ ions activated with a high alkali solution [7,8]. Many researchers [9][10][11][12] reported that the alkali-activated binders provided excellent mechanical and durability properties. Besides, alkali-activated binders showed a lower CO2 footprint than those of PC and epoxy-resin.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Phoo-ngernkham et al [16] and Phoongernkahm et al [17] have shown that the use of FA with additives exhibited the early strength development like the PC system. Thus, it could be used as repair material described in previous studies [10][11][12]18]. Note that the properties of repair material in terms of rapid setting, high strength, high bonding, and high durability are needed.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the AAHFAC could be used as an alternative repair material as reported by several publications [13,14,20,29,[41][42][43]. ere are many reasons such as high compressive strength [44], negligible drying shrinkage [45], low creep [46], good bond with reinforcing steel [47,48], good resistance to acid and sulfate [3,27], fire resistance [49], and excellent bond with old concrete [14,20,28]. For the effect of coarse aggregate size, the strength development tends to decrease with the increase of coarse aggregate size.…”
Section: Resultsmentioning
confidence: 99%
“…It can also give several advantages, such as reducing CO2 emissions, having a high level of workability, more resistant to chemical attack, and resistant to high temperatures [1][2]. The research of [3][4] attempted to utilize waste material as an alternative for repair material. Study of [5] investigated the effect of alkali solutions on geopolymer properties.…”
Section: Introductionmentioning
confidence: 99%